DOI: 10.14264/uql.2020.620
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in frailty: the Frailty Index and the male-female health-survival paradox

Abstract: This publication is a 'highly cited paper' (with 62 citations to date) and is placed in the top 1% of papers in the field of Clinical Medicine in 2017 (Scopus 2019). This manuscript is incorporated into Chapter 2.. Author Contribution E Gordon (candidate) Systematic review and data collection (100%) Data analysis (25%) Data interpretation (100%) Wrote and edited manuscript (80%) Response to reviewers' comments (100%) N Peel Edited manuscript (5%) M Samanta Data analysis (75%) O Theou

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 185 publications
(390 reference statements)
2
1
0
Order By: Relevance
“…Our novel finding of a decreasing magnitude of the association between ACEs and frailty across age groups in men but not women requires further research: it is not clear whether the burden of childhood traumatic experiences is greater and therefore has greater longevity in women, or is instead due to a survival bias, given that women are more likely to live longer than men, despite higher rates of frailty. The latter reason is in line with a potential healthy survivor bias found in older men in our study [42]. Additional longitudinal studies of young and middle-aged adults will be critical in order to parse these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Our novel finding of a decreasing magnitude of the association between ACEs and frailty across age groups in men but not women requires further research: it is not clear whether the burden of childhood traumatic experiences is greater and therefore has greater longevity in women, or is instead due to a survival bias, given that women are more likely to live longer than men, despite higher rates of frailty. The latter reason is in line with a potential healthy survivor bias found in older men in our study [42]. Additional longitudinal studies of young and middle-aged adults will be critical in order to parse these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have shown that the prevalence of frailty is higher in females than in males, even in the same age group. However, the mortality rate of older men is higher than that of older women [7,8], which is known as the "sex-frailty paradox" [8,27]. Furthermore, our ndings support the abovementioned paradox.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, our ndings support the abovementioned paradox. Sex differences in genetic, biological, or psychosocial factors as well as in physiological reserve, burden of disease, and disability might contribute to this paradox [8,27]. However, our data suggested that a potentially unrecognized factor -polypharmacy -might contribute differentially to mortality in the male and female groups.…”
Section: Discussionmentioning
confidence: 85%